(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
Sharp climate changes pose serious risks such as reduced water resources, an increase in natural disasters, and a decline in agricultural productivity, which altogether hinder the sustainable development of our region. These consequences primarily have a negative impact on vulnerable segments of the population